American Precious Metals and their Consequences for Early Modern Europe - Nuno Palma (European Historical Economics Society (EHES), 2019)
Over the early modern period and beyond, massive amounts of silver and gold were found and mined in the Americas. In this paper, I review the consequences for the European economies. Some second-order receiver countries such as England benefited in both the short and long run. First-order receivers such as Spain and Portugal also benefited in the short-run, but their continued exposure to the arrival of massive quantities of precious metals eventually led to loss of competitiveness and an institutional resource curse.
Keywords: E02; E4; N14; O11; 330; American Precious Metals; Early Modern Period; Dutch Disease; Political Institutions; Economic growth; comparative development